Wychowanie sumienia zadaniem pedagogów? - Marek, Zbigniew (Horyzonty Wychowania, 2017)
On the basis of observations made indicating a visible deficiency of what we call man’s conscience, the author poses questions about the reasons for the ensuing situation. Therefore he poses questions about the essence of educating man’s conscience and the possibility of appropriate control over the processes, which will rouse and properly shape pupils’ consciences.The second question posed refers to the possibility and scope of educational efforts undertaken by educator, in order to secure the properly shaped pupils’ consciences. One of the possible answers to these questions is seen in the necessity to relinquish, in the entire moral education processes, any forms of liberalism involving issuing orders or moral imperatives. However, a contraindication against such forms of education may be indicating the only correct form of teaching, how to choose good in life and be guided by this. Transferring the above assumptions onto the grounds of educational practice, the author emphasizes the need for teaching pupil to single out the intentions, he is going to be guided by in his conduct. He also notices that within this scope of educational impact, many positive elements in conscience formation processesmay be, in the case of believers, brought in by referringto God. What justifies this claim is the conviction that belief in God gives man an organized image of the world, and also kindlesthe ability to put things in order, love, which guides man in hisconduct. And this allows pupil to find a real sense of his life withgreater easiness.